Liver Imaging and Detection of Liver Metastases with 99mTc-HIDA - Schulze, P.-J.; Stritzke, P.; Stolzenbach, G. (Nuklearmedizin - NuclearMedicine, 1981)
16 patients with a history or suspicion of malignant disease were investigated scintigraphically for liver metastases. Each patient was studied with 99mTc-HIDA and 99mTc-sulphur- or tin-colloid. In 4 patients liver metastases were suspected and confirmed by ultrasonography and/or computerized tomography. The filling defects were visible with 99mTc-colloids and 99mTc-HIDA as well. Likewise both radiopharmaceuticals coincided in their parenchymal activity patterns in the non-suspicious livers. Because of this good agreement the morphologic aspect of basically functional 99mTc-HIDA examinations is emphasized.